Information search behavior and tax consultants’ recommendation: experimental examination on the role of social norms - Misra, Fauzan; Sugiri, Slamet; Suwardi, Eko; Nahartyo, Ertambang (Journal of Business Economics and Management, 2020)
This study examines the influence of client preference with respect to information search behavior and subsequent tax recommendation. Prior studies have identified that tax consultants exhibit confirmation bias in their information search processes, which is explained by the theory of motivated reasoning (Kunda, 1990). However, that theory does not take into consideration responses of tax consultant that are attributable to the way clients present their preferences. This study fills the gap by proposing a social norm activation model which can help to foster a better understanding of the nature of the confirmatory behavior. To accomplish this purpose, study participants role-played as advisors on a tax compliance task. The experiment used aweb-based instrument that involved 82 tax professionals. Results showed that tax consultants engaged inlower confirmation bias when they received an explicitly preference statement from their client than those who received an implicit statement. Furthermore, the former tax consultants recommended a more conservative tax position than the latter. These findings underscore the importance of social norm in a professional tax work environment. As a practical contribution, these findings suggest that the beliefs and norms of tax professionals influence the way they do their work. First published online 3 January 2020